Synthesis of Air Stable Fused Bicyclic D4-1,2,4-oxadiazoline Platinum(II) Complexes via [2+3] Cycloadditions - Lasri, Jamal (Asian Journal of Chemistry, 2015)
The reaction of trans-[PtCl2(NCR)2] [R1 = CH2CO2Me (1a), R2 = CH2Cl (1b)] with pyrroline N-oxide −O+N=CHCH2CH2CMe2 (2) furnishes, via [2+3] cycloaddition, new fused bicyclic D4-1,2,4-oxadiazoline platinum(II) complexes trans-[PtCl2{N=C(R)ONC(H)CH2CH2CMe2}2] (R1 = CH2CO2Me (3a), R2 = CH2Cl (3b)). Compounds 3a and 3b were refluxed in CH2Cl2 to afford the derived ketoimine platinum(II) complexes trans-[PtCl2{N(C(=O)(R))=CCH2CH2C(Me2)NH}2] (R1 = CH2CO2Me (4a), R2 = CH2Cl (4b)), respectively, as a result of the N-O bond cleavage of the oxadiazoline ring in compound 3. All the platinum complexes were characterized by IR, 1H and 13C NMR spectroscopies, ESI+-MS and elemental analyses.